OP0239 Comprehensive Analyses of Lung Abnormalities on Chest Computed Tomography in Patients with Microscopic Polyangiitis before Receiving Immunosuppressive Treatment. (9th June 2015) - Yamagata, M.; Ikeda, K.; Tsushima, K.; Iesato, K.; Abe, M.; Ito, T.; Kashiwakuma, D.; Iwamoto, I.; Nakagomi, D.; Sugiyama, T.; Furuta, S.; Jayne, D.; et al.
Abstract : Background: Lung is one of the major organs involved in microscopic polyangiitis (MPA) and recent studies have demonstrated that pulmonary involvement is associated with unfavorable outcomes (1). Although a previous histopathological study showed that a wide variety of extravascular pulmonary injuries can be present in MPA lung, the prevalence of these lung abnormalities has not been determined. Objectives: In this study, we aimed to determine the prevalence of lung abnormalities on the chest computed tomography (CT) in patients with MPA before receiving immunosuppressive treatment and assess their associations with patient/disease characteristics. Methods: We retrospectively identified 167 hospital-based consecutive MPA patients in three centers in Japan. Of these patients, we collected clinical information of 150 patients whose CT images before treatment were available. Three pulmonologists determined the presence/absence of 22 CT imaging components for interstitial, emphysematous, airway, pleural, and miscellaneous lung lesions. Results: Eighty-nine patients (59%) were female and mean age was 70 (range 42-89). The vast majority (91%) were positive for myeloperoxidase (MPO)-anti-neutrophil cytoplasmic antibodies (ANCA) and had high systemic vasculitis activity (median Birmingham Vasculitis Activity Score [BVAS] 18; median serum C-reactive protein [CRP] level 85.1 mg/L). A wide variety of lung abnormalities on the chest CT images were identified in most of the patients (97%), including interstitial lung lesions (66%), airway lesions (66%), pleural lesions (53%), and emphysematous lesions (37%). Agreement between independent readings by two readers was moderate or greater (kappa >0.40) on all items but the cystic emphysematous lesion (kappa =0.39). Despite the high prevalence of interstitial lung lesions, we identified only 14 patients (9%) whose chest CT scan showed a global pattern of lung abnormalities that fit into previously reported interstitial pneumonia (IIP) patterns. In multivariate analyses, ground-glass opacity was associated with BVAS, whereas three out of four airway lesions were associated with MPO-ANCA. Latent class analysis identified three groups of the clustering patterns of these lung abnormalities. These groups were characterized by the interstitial lung lesions which accompanied other lesions (Class 1), the airway lesions (Class 2), and the paucity of parenchymal or airway lesions (Class 3), respectively (Figure ). Patients with IIP patterns were all classified as Class 1. Conclusions: Abnormalities in a wide range of anatomical areas can be identified in the lung of MPA patients before treatment. Our data reveal a subgroup of patients with airway-predominant pulmonary involvement that is associated with MPO-ANCA. The prevalence and the clustering patterns of individual lung abnormalities provide groundwork to inform future studies to understand the pathophysiology of MPA. References: Furuta S, Chaudhry AN, Hamano Y, et al. Comparison of phenotype and outcome in microscopic polyangiitis between Europe and Japan. J Rheumatol 2014;41:325-33. Disclosure of Interest: None declared